"I think people should be more aware:" Uterine fibroid experiences among women living in Indiana, USA. (February 2023) - Dykstra, Chandler; Laily, Alfu; Marsh, Erica E.; Kasting, Monica L.; DeMaria, Andrea L.
Abstract: Objective: To understand healthcare experiences among patients with uterine fibroids (fibroids) across the continuum of care, from early symptoms through diagnosis, treatment, and management, while also investigating health disparities. Methods: We conducted 20 semi-structured interviews with patients with fibroids. Interviews were transcribed verbatim and qualitatively analyzed using thematic analysis. Eligible participants were women aged 18 and over, residing within 75 miles of one of the two recruitment locations (Tippecanoe or Marion County) in Indiana, USA. Results: Women experienced myriad physical symptoms, which often manifested into psychological and sexual disturbances and infiltrated all aspects of daily life. Internet searches were frequently mentioned as their main information source. Fertility became a prominent factor in deciding treatment options. However, health disparities prevented some from receiving quality fibroids healthcare. Some women reported staying home during COVID-19 pandemic facilitated the management of physical symptoms. Overall, participants advocated for greater fibroids awareness and education. Conclusion: Results highlight barriers and facilitators to fibroids-related decisions, behaviors, and outcomes. Translation of research to practice was guided by a combined Social-Ecological Model and social determinants of health framework for development of strategic interventions. Practice Implications: Interventions should aim to improve fibroids healthcare access, education and awareness, and patient-provider communication for minority, rural, and low socioeconomic status communities disproportionately impacted by fibroids. Highlights: Explore the experiences of patients with uterine fibroids across the continuum of care. This work contributes to the limited body of qualitative research on fibroids. Results capture fibroids experiences of minority, rural, and low socioeconomic status communities. Health disparities prevented some from receiving quality fibroids healthcare. Practical recommendations can improve fibroids awareness, treatment, and management.